If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + p = -40 Solving -15 + p = -40 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + p = -40 + 15 Combine like terms: -15 + 15 = 0 0 + p = -40 + 15 p = -40 + 15 Combine like terms: -40 + 15 = -25 p = -25 Simplifying p = -25
| 1b+4=2b-5 | | -C-29=13+2x | | -9q-5x+2= | | 57=3t | | 2s-3p-4= | | y=2x^4-x^3-5x^2+2x+2 | | 2-5y=32 | | 3z*z+12z=0 | | -5(2)(3)(-4)= | | 360x=4071.6 | | 3ab/3ab | | 9y-4=y-z | | 10x-x^2/2 | | 3zsquared+12z=0 | | 2y+5y-3-4=4y-y+9-3y | | 6ap+15a-4p-10= | | 22x+3=33x | | 0.15a-0.15a=0.03(4a+4) | | 6x+15y=-30 | | 3c^2=75 | | 2.1+-5=9.32 | | (25a^2b^2)^1/2 | | 8x/2y | | A+b+y+s+e=bs | | -(6+8n)=-4+7(-n+2) | | 8x-12-3x= | | -2(3x+1)+3(x+4)= | | z/10=12 | | m+5m=3m-21 | | 360x=12254.5 | | (5x^2-7x+3)=0 | | 18=r-7 |